Whose Troy? Whose Rome? Whose Europe? Three Medieval Londons and the London of Derek Walcott’s 'Omeros' (Interfaces: A Journal of Medieval European Literatures, 2019)
What does it mean that so many medievalists, especially in the United States and in Canada, study the European middle ages without being from or of Europe? What does it mean if we specify, further, those who don’t come from the United States or Canada either, but from areas of the world that experienced western European empire, as most of the globe did, as a systematic political and psychological subordination to Europe? I take the Caribbean poet Derek Walcott’s depiction of late twentieth-century London in his long narrative poem Omeros as a way to pose the question of what Europe might look like from the other side of the relationship of domination, that is, to define Walcott’s Europe. Walcott’s London repudiates Europe, and with it what he calls History, exactly the kind of history made by the European epics of Homer, Virgil, and Dante in the form of the world-destinies they constructed for Europe in the cities of Troy and Rome, and made by their would-be successor London. But he does so with difficulty: the Troy of Homer and Virgil has long sought to seduce him into rendering his own island into its terms, elegiac and nostalgic. He seeks instead a poetry of the local, the small, the unvarnished, and the present tense. In doing so, he constructs a point of view that exposes the presumption and the brutality that sits inside medieval texts offered to the reader as celebrations of London and the history it contributes to making; but his perspective also brings out of the same texts their half-conscious efforts, repressed in the name of History, to speak for the local, the small, the unvarnished, and the present, on behalf of the desire for human adequacy to self, sociality, and community without war. Roughly speaking, desire, or history, shows up in the view from Walcott’s St. Lucia in the face of the History for which Europe is a metonym. Medieval texts read from outside the European frame are liable to be different from those read from within that frame; we need medieval readings from underneath and outside the European matrix that can put Europe in question, though it may be that History, and the project of a dominating Europe, remains too seductive to renounce.
Keywords: Derek Walcott; Homer; Geoffrey of Monmouth; epic; empire